2009
DOI: 10.1016/j.jad.2009.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Pain and depression in older people: Comorbidity and patterns of help seeking

Abstract: The cross-sectional nature of this study does not allow determination of direction of causality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 18 publications
6
34
1
1
Order By: Relevance
“…But our sample had mild depressive symptoms according to the GDS. Although there have been some finding indicating that chronic musculoskeletal pain increases depressive symptoms in older adults, our results did not support this idea26, 27 ) .…”
Section: Discussioncontrasting
confidence: 95%
“…But our sample had mild depressive symptoms according to the GDS. Although there have been some finding indicating that chronic musculoskeletal pain increases depressive symptoms in older adults, our results did not support this idea26, 27 ) .…”
Section: Discussioncontrasting
confidence: 95%
“…Major depression is associated with high numbers of medically unexplained symptoms 28-30 , such as pain and fatigue, and poor general health outcomes 1, 31 . Untreated depression is independently associated with morbidity 31-34 , delayed recovery and negative prognosis among those with medical illness, elevated premature mortality associated with comorbid medical illness 35 and increased health care costs 36-38 . Depression also increases functional impairment 39-44 and decreases work productivity 45 .…”
Section: Interaction Of Depression With Other Chronic Illnessesmentioning
confidence: 99%
“…Pain can give rise to physical incapacitation followed by depression due to reduced physical and social activities [5, 6]. Bonnewyn et al [7] found that painful physical symptoms are associated with major depressive disorder and influence help seeking as well as use of medication. Suen and Tusaie [8] reported that depressed persons exhibited guilt, sadness, anger, resentment, loneliness, helplessness, hopelessness, inability to enjoy activities, and anhedonia.…”
Section: Introductionmentioning
confidence: 99%